2016
DOI: 10.1016/j.biomaterials.2016.01.056
|View full text |Cite
|
Sign up to set email alerts
|

Viral-mimicking protein nanoparticle vaccine for eliciting anti-tumor responses

Abstract: The immune system is a powerful resource for the eradication of cancer, but to overcome the low immunogenicity of tumor cells, a sufficiently strong CD8+ T cell-mediated adaptive immune response is required. Nanoparticulate biomaterials represent a potentially effective delivery system for cancer vaccines, as they can be designed to mimic viruses, which are potent inducers of cellular immunity. We have been exploring the non-viral pyruvate dehydrogenase E2 protein nanoparticle as a biomimetic platform for canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(109 citation statements)
references
References 53 publications
3
106
0
Order By: Relevance
“…4547 Moreover, it has been shown that nanoparticles are engulfed preferentially by phagocytic myeloid cells and may serve as a mechanism to target these cells and promote a tumor-suppressive environment. 48,49 For example, in a study by Huang et al , a galactosylated cationic dextran nanoparticle-driven nucleic acid delivery system carrying CpG, anti-IL-10, and anti-IL-10 receptor oligodeoxynucleotides was utilized to target tumor-associated macrophages (TAM) to suppress their pro-tumorigenic functions and promote anti-tumor activity.…”
Section: Discussionmentioning
confidence: 99%
“…4547 Moreover, it has been shown that nanoparticles are engulfed preferentially by phagocytic myeloid cells and may serve as a mechanism to target these cells and promote a tumor-suppressive environment. 48,49 For example, in a study by Huang et al , a galactosylated cationic dextran nanoparticle-driven nucleic acid delivery system carrying CpG, anti-IL-10, and anti-IL-10 receptor oligodeoxynucleotides was utilized to target tumor-associated macrophages (TAM) to suppress their pro-tumorigenic functions and promote anti-tumor activity.…”
Section: Discussionmentioning
confidence: 99%
“…1116 We have shown that E2 possesses the capability to simultaneously deliver tumor antigens and CpG to DCs for enhanced activation of antigen-specific CD8+ T cells, yielding enhanced anti-cancer activity and increased survival time of syngeneic tumor-bearing mice. 12, 14 …”
mentioning
confidence: 99%
“…Immunization of mice with protein nanoparticles conjugated to melanoma-associated epitope gp100 and CpG adjuvant enhanced the production of melanoma-specific CD8 + T cells. Pre-immunization with nanoparticles delayed onset of tumor growth and increased the survival rate to 40%, showing prophylactic potential of protein nanoparticles [59] . Luo et al, showed strong cytotoxic T cell response by a physical mixture of PC7A polymeric nanoparticle and OVA antigen.…”
Section: Nanovaccine For the Prevention Of Cancermentioning
confidence: 99%
“…Cages like 25 nm E2 cage derived from the pyruvate dehydrogenase complex of Bacillus stearothermophilus [59] , 13 nm cage of human heavy chain ferritin (an iron storage protein) [60] , ~24 nm encapsulins (class of icosahedral cage structures) of bacteria and archaea are used for the presentation of different antigens to elicit immune response after immunization [61] . A recent study on nonviral E2 protein-based biomimetic nanoparticle-containing acidlabile CpG (DC activating molecule) and SIINFEKL peptide epitope conjugate has shown the potential to enhance the CpG mediated DC activation by 25-fold in vitro as compared to unbound CpG.…”
Section: Protein/peptide-based Nanovaccinesmentioning
confidence: 99%